Downregulation of UDP-glucose 6-dehydrogenase predicts adverse outcomes in patients with colorectal cancer and promotes tumorigenesis - Mengyuan Wang; Zhiming Ge; Xianxian Fan; Hongbo Zhao; Zhenfu Shi; Jiucun Zhang; Li Jin; Yan Li; Jie Wang; Xiaobin Zao; Yun Yang (Scientific Reports)
Abstract UDP-glucose 6-dehydrogenase (UGDH) is the key enzyme of glucuronic acid metabolism and a key mediator in several cancer developmental signaling pathways. However, the expression and function of UGDH in colorectal cancer (CRC) are unclear. Bioinformatics analysis was conducted to research the expression, diagnosis, prognosis, functional enrichment, genetic alterations, and immune characteristics of UGDH in CRC. Hematoxylin-Eosin staining, KI67 immunohistochemistry staining, and UGDH immunohistochemistry staining of clinical colon tissues were performed. The UGDH gene was knocked down in HCT-8 cells. CCK8 and cell wound scratch assays were further performed in UGDH wild-type and UGDH-knockdown HCT-8 cells. UGDH is markedly downregulated in CRC tissues compared to normal tissues, which predicts a poor prognosis. The lower expression of UGDH is associated with a high gene promoter methylation level and genome deletion. UGDH expression is proportional to immune cell infiltration and immune-related genes. UGDH expression is correlated with the p53 signaling pathway. Knockdown of UGDH in HCT-8 cells promoted their proliferation and migration ability. UGDH could be useful as a valuable prognostic biomarker and potential therapeutic target in CRC. UGDH could inhibit the proliferation and migration of CRC cells.